The Policy of Coastal Waste Management: Case Study In Demak Regency - Masrohatun, Masrohatun (Departemen Ilmu Administrasi FISIP UNHAS, 2022)
The excessive amount of waste piles has been a challenge for Indonesia. Moreover, it has worse impact on coastal communities as rob takes place. Hence, this study aims to unveil the forms of coastal community waste management and local government policy. Using qualitative method and case study approach, it was found that coastal communities shared the same understanding of waste. They perceived it as discarded substance, both organic and inorganic, after its primary use. Further, coastal communities disposed of the waste by getting it burnt, buried, thrown into rivers, sold, and saved in waste banks. In dealing with waste problems, the government issued policies by signing cooperation agreements and encouraging residents to have waste management literacy. However, many village governments did not have any specific policy on waste management.